Professional Mobility and “Objective” and “Subjective” Satisfaction. a Non- Linear Analysis from the Theory of the Three-Dimensional Spiral of Sense in Population of Doctors - Aparicio, Miriam Teresita (2016)
This work goes along the lines of the author’s research (1995-2016) on professional careers and models bearing causes and effects regarding sustained interaction (core, psychosocial, institutional and structural factors). The aim of this paper was analyze, through the doctors’ social representations, the levels of satisfaction evidenced by those who have advanced professionally to the highest positions within the scientific (or other) system. The hypothesis states that the relation is not linear but inverse. Satisfaction would not increase according to the Professional Status. We consider here, on the one hand, the insufficient Professionalization and the increasing demands from the market; and on the other, the impact structural limits have on the micro level. The methodology used was quanti-qualitative (semi-structured questionnaires, interviews, and hierarchical evocations). The population consisted of doctors (2005-2012) from the National University of Cuyo, in Argentina and the Cnam (France) of different courses of study. The results confirm the hypothesis. As regards what was observed among those who advanced professionally, the increase on the growing market demands along with the lack of institutionalized means in order to reach goals, result in lower satisfaction. This is interpreted from the theory of the author, which involves 3 levels (macro-meso-micro-macro) (Aparicio, 2015 a, b). We also consider the theories of anomie and of the expectancy of valence (Feather - Davenport). Findings along this line were also seen in studies with scientists (Aparicio, 2014). The results propose a revision in the prevailing working conditions and police: satisfaction acts on subsystems and consolidates them.